Prion Amyloid Polymorphs – The Tag Might Change It All - Bousset, Luc; Luckgei, Nina; Kabani, Mehdi; Gardiennet, Carole; Schütz, Anne K.; Melki, Ronald; Meier, Beat H.; Böckmann, Anja (Frontiers in Molecular Biosciences, 2020)
Sup35p is a protein from Saccharomyces cerevisiae. It can propagate using a prion-like mechanism, which means that it can recruit non-prion soluble Sup35p into insoluble fibrils. Sup35p is a large protein showing three distinct domains, N, M and an extended globular domain. We have previously studied the conformations of the full-length and truncated NM versions carrying poly-histidine tags on the N-terminus. Comparison with structural data from C-terminally poly-histidine tagged NM from the literature surprisingly revealed discrepancies. Here we investigated fibrils from the untagged, as well as a C-terminally poly-histidine tagged NM construct, using solid-state NMR. We find that the conformation of untagged NM is very close to the N-terminally tagged NM and confirms our previous findings. The C-terminal poly-histidine tag, in contrast, drastically changes the NM fibril structure, and yields data consistent with results obtained previously on this construct. We conclude that the C-terminally located Sup35p globular domain influences the structure of the fibrillar core at the N domain, as previously shown. We further conclude, based on the present data, that small tags on NM C-terminus have a substantial, despite different, impact. Modifications at this remote localization thus shows an unexpected influence on the fibril structure, and importantly also its propensity to induce [PSI+].